Strategi Meningkatkan Kapasitas Mahasiswa dalam Berorganisasi - Sahdan Sahdan (CV. Lenggogeni Data Publishing, 2023)
The increase in population accompanied by the weak competence of university graduates has caused the unemployment rate in Indonesia to increase quite significantly. This of course requires students as the nation's next generation to have superior competence to contribute to bringing about a change, therefore it is necessary to increase the capacity of students in order to prepare themselves as the hope for the nation in the future. Student organizations are a place that is able to develop students' capacity to be better, through participation in organizations, students can develop the competencies that exist in themselves. This study aims to analyze the capacity building that students have when they participate in an organization. The method used in this study is qualitative with a descriptive analysis approach. This research was conducted at the Islamic Education Management Student Association as one of the intra-campus student organizations. The results of the study show that students who are actively involved in organizations have superior competence compared to students who are only active in the academic field. In the process students can develop some of the competencies they have within the organization including: (1) practicing Critical Thinking skills (2) Building student Character (3) Increasing Solidarity and (4) Practicing Leadership skills